Return On Investment (Roi) terhadap Harga Saham - Andina Dwijayanti (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2019)
This research aims to determine the effect of Return on Investment on the Share Price of PT Astra International. The period used in this study is the period 2013-2018. The population in this study is a mining company registered with IDX. Sample selection using purposive sampling methods. A total of 31 mining companies were registered with IDX in the period 2008-2010. The data analysis used to test hypotheses is to use simple regression analysis techniques. Based on the results of the study showed that the results of statistical processing obtained a value of significance of 0.935 is greater than the criteria of significance (0.05). Thus the regression model is insignificant. This means that linear regression does not meet the criteria of linearity. The r2 value of 0.002 means the variability of dependent variables that can be explained by independent variable variability of 0.2% while the remaining 99.8% is explained by other variables not included in the regression model.